Geopolymer Synthesis and Alkaline Activation Technique of Fly Ash and Slag Source Material: A Review - Erunkulu, Ibukun; Malumbela, Goitseone; Oladijo, Oluseyi Philip (Applied Science and Engineering Progress, 2023)
The advent of geopolymer and its synthesis from industrial waste rich in silicon and aluminum activated by an alkaline solution has proven a viable alternative to ordinary Portland cement. This review presents background on alkaline activation, geopolymerization technology as well as industrial aluminosilicate-based geopolymeric products produced from a range of low to high calcium fly ash, and metallurgical slags in different combinations. Important synthesis conditions, such as the nature of the source material, the type of alkaline activator, the curing condition, and the mixing procedure were effective determinant factors for desired properties in products. The significance of these parameters on the mechanical performance of products relative to each other is discussed. Advances in synthesis, material processing, and production, such as solid-state mechanism and one-part activation are also presented. Future recommendations on other aluminosilicate sources to be considered are highlighted.